Associations between parenting stress, parent mental health and child sleep problems for children with ADHD and ASD: Systematic review. (October 2019) - Martin, Christina A.; Papadopoulos, Nicole; Chellew, Tayla; Rinehart, Nicole J.; Sciberras, Emma
Highlights: Examines family functioning and child sleep for children with ADHD and ASD. Parenting stress and sleep problems are associated for children with ASD. Sleep problems and parenting stress have not been examined for children with ADHD. Parent mental health and child sleep are associated for children with ADHD and ASD. More research is needed given the absence of bidirectional relationship research. Abstract: Background: Children with attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) experience high rates of sleep problems. Their parents experience higher parenting stress and more mental health difficulties than parents of typically developing children. Aim: To examine the association between child sleep problems, parenting stress and parent mental health for children with ADHD or ASD. Methods: MEDLINE Complete, EMBASE, PsycINFO and CINAHL Complete databases were searched. Studies needed to include: children aged 5–18 with ADHD or ASD, a child sleep measure, and a parenting stress or adult mental health measure. Results: Eleven studies were identified (four ADHD, seven ASD). Six studies examined parenting stress (five cross-sectional, one longitudinal) and five found associations, of varying strengths, with child sleep problems. Six studies examined parent mental health (four cross-sectional, two longitudinal) and five found associations, of differing magnitudes, with child sleep problems. Conclusions: These studies demonstrate child sleep problems are associated with poorer parent mental health and higher parenting stress. Implications: Future longitudinal research including multiple measurements of child sleep problems and family functioning is required to clarify the directionality of associations. Such knowledge is key in adapting sleep interventions to better meet the needs of children with ADHD or ASD and their families.